Nice Dig! : An Analysis of the Verbal and Visual Coverage of Men’s and Women’s Beach Volleyball During the 2008 Olympic Games - Smith, Lauren Reichart and Bissell, Kimberly L. (Communication & Sport, 2014)
This study represents a content analysis of 10 beach volleyball games for the men’s and women’s team USA during the 2008 Summer Games. Play-by-play commentary and between-play commentary were analyzed for all 10 games, and all court shots and camera angles were coded. Using earlier work examining the existence or presence of gender inequities in mediated coverage of sport in general, the goal was to identify how or if coverage of beach volleyball might still reinforce gender inequities. Findings from the coded visual and verbal coverage suggest that gender difference was not evident in the manifest content of the 2008 Olympic Games. Additional findings and implications are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMTY3NDc5NTEyNDY3Nzcx